Service Quality and Citizen Experience in Integrated Public Services: Evidence from the Public Service Mall of Madiun Regency - Wisnu Adinugroho; Harianto Harianto; Agus Wiyaka (Universitas Negeri Surabaya, 2026)
Public Service Malls (Mal Pelayanan Publik/MPP) were developed in Indonesia to improve the accessibility, efficiency, and integration of public services through a one-stop service system. This study aims to analyze the quality of public services at the Public Service Mall of Madiun Regency using the SERVQUAL dimensions: tangibles, reliability, responsiveness, assurance, and empathy. A qualitative case study approach was employed to obtain an in-depth understanding of service implementation from the perspectives of both service providers and service users. Data were collected through observations, semi-structured interviews, and documentation involving six informants consisting of service officers from Dukcapil, DPMPTSP, BPJS, and Bapenda, as well as two community members. Data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings show that the overall quality of public services at the MPP of Madiun Regency is relatively good. Adequate facilities, consistent procedures, responsive officers, professional service attitudes, and empathetic interactions contribute positively to public service experiences. However, several challenges remain, including queue congestion, unstable digital systems, limited infrastructure, and the use of administrative language that is difficult for some users to understand. The study concludes that strengthening digital infrastructure, communication clarity, queue management, and human-centered service practices is important for improving integrated public service quality.